Evaluation of the Implementation of the Independent Teaching Platform (PMM) in Improving the Quality of Geography Learning in Temanggung Regency - Sri Peni; Muhammad Nursa’ban (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The Merdeka Mengajar (PMM) platform was developed as a support tool for teachers in understanding and implementing the Merdeka Curriculum. However, the utilization of this platform by high school geography teachers in Temanggung Regency is still relatively low. This study aims to: 1) evaluate the level of understanding of high school geography teachers in Temanggung Regency regarding the facilities available in PMM; 2) evaluate teacher planning in utilizing PMM to support the implementation of the Merdeka Curriculum; 3) evaluate the implementation of PMM utilization in the Merdeka Curriculum implementation process; and 4) evaluate the results of PMM utilization in supporting the implementation of the Merdeka Curriculum by high school geography teachers. This study is an evaluative study with a descriptive approach using the Discrepancy Evaluation Model (DEM). The variables studied include the level of understanding, planning, utilization, and results of PMM utilization in the learning process and assessment. The study population was all high school geography teachers in Temanggung Regency who have belajar.id accounts. The research subjects were 16 geography teachers from 11 schools. The results of the study indicate that: 1) high school geography teachers in Temanggung Regency have a good level of understanding of the PMM facility as a supporting tool for the implementation of the Independent Curriculum; 2) teachers have good planning in utilizing PMM; 3) the implementation of PMM utilization is in the sufficient category; and 4) the implementation of the Independent Curriculum by geography teachers is in the good category. These findings indicate that PMM is not yet fully effective as the sole learning resource in supporting the implementation of the Independent Curriculum, because teachers still utilize various other learning resources that contribute to their ability to implement the curriculum